2016
DOI: 10.1007/s11368-016-1542-y
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal and PCB spatial distribution pattern in sediments within an urban catchment—contribution of historical pollution sources

Abstract: Purpose This work analyzes polychlorinated biphenyl (PCB) and heavy metal contamination in fluvial sediments and soils in an urban catchment, according to the geo-accumulation index and to soil and sediment quality guidelines. The catchment is located in Coimbra, Portugal, being affected by frequent flooding, and its main stream is a tributary to one of the major rivers in Portugal (Mondego). Given the presence of industrial activities over time, some inputs of pollutants are expected, but so far, the legacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…These distribution changes were in accordance to findings by [26]. Two aspects of the spatial distribution of surface PCBs are the anthropogenic PCB production and the associated discharges from land [24,26,[64][65][66][67][68]. Though their production is currently banned by the Stockholm Convention (http://www.pops.int/access 09.12.2019), these contaminants are still entering the environment via leaching and weathering from already existing products.…”
Section: Spatial-temporal Variability In Pcbsupporting
confidence: 84%
“…These distribution changes were in accordance to findings by [26]. Two aspects of the spatial distribution of surface PCBs are the anthropogenic PCB production and the associated discharges from land [24,26,[64][65][66][67][68]. Though their production is currently banned by the Stockholm Convention (http://www.pops.int/access 09.12.2019), these contaminants are still entering the environment via leaching and weathering from already existing products.…”
Section: Spatial-temporal Variability In Pcbsupporting
confidence: 84%
“…Pollutants deriving from urban areas include heavy metals [31], PCBs [47], nutrients [48], pesticides [44], pharmaceuticals [49] and faecal coliforms [50]. Sources of water pollution in urban areas can include (i) industrial processes and spills [51], (ii) untreated solid waste disposal and leachate from landfills [52], (iii) wastewater contamination from septic tanks, leakages in sewage systems and inefficient wastewater treatment [53], (iv) stormwater runoff [31,54], (v) lawns and gardens maintenance due to inappropriate fertilization and irrigation [55], (vi) soil erosion [56], and (vii) atmospheric deposition [30].…”
Section: Deterioration Of Water Quality and Impacts On Aquatic Ecosysmentioning
confidence: 99%
“…Urban streams, however, typically display reduced baseflow due to lower groundwater contributions [38,43], although sometimes water and sewer leakages within artificial drainage systems may enhance this streamflow component [44].Urban areas comprise varying spatial mosaics of paved/sealed surfaces and green areas.Different combinations and spatial arrangements of impervious and pervious surfaces greatly affect the rainfall-runoff process, as well as the connectivity between land surface and the drainage network, and thus the speed and magnitude of runoff delivery to the stream[17,42]. For example, Ferreira et al[47] recorded response times three times shorter in urban sub-catchments with continuously built-up areas located downslope, than with M A N U S C R I P T A C C E P T E D 9 peaks and total streamflow than piping into adjacent areas of permeable soil[40].Conventional piped drainage leads to four times greater runoff than a swale drainage system[19].…”
mentioning
confidence: 99%
“…Contemporary studies [2,[5][6][7][8][9][10] revealed that storm water run-off carried metals originating from a variety of everyday activities associated with tire wear, corrosion, roof run-off and fuel combustion products. It is well established that run-off from urbanized catchment is abundant in HMs [11][12][13]. However, little is known as regards the influence of the run-off from urbanized catchment composed of soft, natural surfaces (forest, lawns, gardens) vs run-off from 2 of 14 paved surfaces (roads, sidewalks, squares, fuel stations) on the metals levels in the run-off receivers.…”
Section: Introductionmentioning
confidence: 99%